AUGMENTED REALITY BASED HUMAN DIGESTIVE ORGAN LEARNING APPLICATION WITH MULTI MARKER METHOD - Ellen Pratama; I Gusti Ngurah Suryantara (Jurnal Teknik Informatika (Jutif), 2022)
Technology has been used by all ages, including children, because technology can be applied in many fields, including education. In education, there is learning about the human digestive organs, which is still taught in the conventional way because they use learning media such as books, but it is still lacking for students to visualize the organs. Efforts are needed to solve this problem by developing learning media that apply augmented reality technology in the form of learning applications. The learning application developed is called ORCEMAR, which has two menus, namely the learning and evaluation menu. The learning menu uses augmented reality technology with a multimarker, and the evaluation menu is a quick quiz that has a score calculation feature using the fuzzy tsukamoto algorithm. Based on alpha testing, the multimarker method was successfully implemented, and the features and components of the application worked well. The application is compatible with Android 5.1 to Android 10, with a minimum camera resolution of 13 MP and 2GB RAM. Based on beta testing collected through questionnaires, the percentage of 40 respondents who are 5th grade elementary school students who answered that the components and features of the application work well above 50%, and also more than 50% of the respondents answered "yes" to the question asking if the application can increase interest, understanding, and also The application can be a complement to conventional learning media to study human digestive organs. Based on this research, the ORCEMAR application was successfully developed and the multimarker method was successfully implemented, as well as features and components that functioned well and received a good response from the target audience.